2013
DOI: 10.1002/col.21823
|View full text |Cite
|
Sign up to set email alerts
|

Brightness scaling according to gamut relativity

Abstract: Brill and Carter [Color Res Appl (DOI:)] rekindle the question of whether brightness scaling is better approximated by a log or power function, proposing on theoretical and empirical grounds that the log function is the correct choice. This note provides a new twist to this debate in terms of a recently introduced theory of brightness and lightness perception, called gamut relativity. The theory reconciles the log and power function formulations and approximately predicts the weight/exponent values associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The restatement of several extant computational problems of visual surface representation in terms of gamut relativity provides a new perspective on the nature of computational vision [53][54][55][56]. Rather than postulating a reified mapping from physical dimensions to perceptual dimensions, gamut relativity suggests how properties such as lightness, transparency, and gloss emerge naturally through a process of vector computation operating in blackness-whiteness space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The restatement of several extant computational problems of visual surface representation in terms of gamut relativity provides a new perspective on the nature of computational vision [53][54][55][56]. Rather than postulating a reified mapping from physical dimensions to perceptual dimensions, gamut relativity suggests how properties such as lightness, transparency, and gloss emerge naturally through a process of vector computation operating in blackness-whiteness space.…”
Section: Discussionmentioning
confidence: 99%
“…The model is framed within the context of a broader computational theory, termed gamut relativity, that has previously been used to explain a wide body of psychophysical data on brightness, lightness, and transparency perception involving diffusely reflecting surfaces [53][54][55][56]. Here I extend the theory to the domain of specularly reflecting surfaces in order to explain key aspects of gloss and lightness perception in a unified manner.…”
Section: Introductionmentioning
confidence: 99%
“…A lighter surround has a very great impact on the appearance of a dark region, while a darker surround has a much smaller impact on the appearance of a light region (Heinemann, 1972; Rudd and Zemach, 2004, 2005, 2007; Vladusich, 2013a,b). Gilchrist (1988) measured the relative influences of dark and light surrounds on identical gray papers in a simultaneous contrast display and concluded that most of the illusion was accounted for by darkness induction from the light surround to the decremental paper.…”
Section: The Basic Neural Edge-integration Modelmentioning
confidence: 99%
“…The cornerstone of their argument is that neutral scale is determined by background luminance, not by background appearance, contrary to the implication of the differential equation generating the power law. Vladusich takes a more general view, associating power‐law scaling of luminance with cortical processing (e.g. estimating magnitude of light intensity, inferring the illuminant) and identifying logarithmic scaling with retinal discriminations (e.g.…”
Section: Discussionmentioning
confidence: 99%